Tindak Pidana Pembunuhan oleh Ibu Terhadap Anak Kandung (Studi Putusan No. 80/Pid.Sus/2018/PN Gianyar) - Ida Ayu Made Wahyuni Dewi; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
The crime of murder is an act against the law that has the aim of taking a person's life, children can also become victims. This study aims to examine the regulation of the crime of murder by a mother against her biological child in Decision No. 80/Pid.Sus/2018/PN Gin and examine the judge's considerations in making a decision against the perpetrator of the crime of murder by the mother of her biological child in decision No. 80/Pid.Sus/2018/PN Gin. This research is designed with a normative research approach to legislation and a case approach. The data sources used are primary and secondary legal data obtained from several related sources using field observation and documentation techniques, then the data is processed and analyzed qualitatively descriptively. The results show that the regulation of the crime of murder by a mother against her child is regulated in Article 80 paragraph (3), (4) of Law No. 35 of 2014 Amendment to Law No. 23 of 2002 on Child Protection regarding violence against children that causes death. The judge's consideration in making the decision No. 80/Pid.Sus/2018/PN Gin, the judge considered the legal facts obtained from the defendant, witnesses and evidence.